2008
DOI: 10.1088/0022-3727/41/17/175212
|View full text |Cite
|
Sign up to set email alerts
|

The characterization of radio-frequency discharge using electrolyte solution as one electrode at atmospheric pressure

Abstract: Atmospheric pressure discharges driven by radio-frequency source were generated using electrolyte solution as one electrode. The electron density calculated from the Stark broadening of Hβ (486.1 nm) was in the order of 1015 cm−3 and showed a parabolic shape with the pH value of the solution. The simulated gas temperature increased from 950 to 2750 K as the input power increased from 12 to 40 W. We found that the plasma exposure was accompanied with the acidification of the solution electrode; it was ascribed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 24 publications
0
21
0
Order By: Relevance
“…Ultraviolet (UV) light is usually observed in the plasma-liquid system [79,80]. Therefore, the high energy of UV photons can be transferred to water molecules, producing potential reducing/oxidizing species, →…”
Section: Plasma Over Liquidmentioning
confidence: 99%
“…Ultraviolet (UV) light is usually observed in the plasma-liquid system [79,80]. Therefore, the high energy of UV photons can be transferred to water molecules, producing potential reducing/oxidizing species, →…”
Section: Plasma Over Liquidmentioning
confidence: 99%
“…Chen et al found a Boltzmann correlation between the increase of the plasma temperature and the increase of the Na emission line. 27 Therefore, it may be assumed that the generation of the atomic potassium in the KCl and KOH solutions determined the increase of the electron temperature ( Fig. 11).…”
Section: Time-resolved Optical Emission and Absorption Spectroscopymentioning
confidence: 99%
“…Recently, APGD plasmas with various liquid electrodes have been studied at different currents and distances from the liquid electrode [11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26], while the other plasma generation parameters were faintly investigated. Nevertheless, the phenomena of glow discharge generated at atmospheric pressure are still poorly understood.…”
Section: Introductionmentioning
confidence: 99%